2018
DOI: 10.1097/aln.0000000000001907
|View full text |Cite
|
Sign up to set email alerts
|

Vasculotide, an Angiopoietin-1 Mimetic, Restores Microcirculatory Perfusion and Microvascular Leakage and Decreases Fluid Resuscitation Requirements in Hemorrhagic Shock

Abstract: Background Microcirculatory dysfunction is associated with multiple organ failure and unfavorable patient outcome. We investigated whether therapeutically targeting the endothelial angiopoietin/Tie2 system preserves microvascular integrity during hemorrhagic shock. Methods Rats were treated with the angiopoietin-1 mimetic vasculotide and subjected to hemorrhagic shock and fluid resuscitation. Microcirculatory perfusion and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 32 publications
3
52
1
Order By: Relevance
“…Survival Probability syndrome, and disseminated intravascular coagulation, Angpt-2 upregulation and Tie2 inhibition have been linked to thrombocytopenia, increased INR, elevated D-dimer, overexpression of pro-inflammatory cytokines, multisystem organ dysfunction (e.g., AKI), decreased systemic circulating blood pressure, and ultimately poorer survival; conversely, interventions to restore or enhance Tie2 signaling not only ameliorate these abnormalities but also improve survival. (16,18,23,42) Strikingly, this same constellation of features is present among patients with decompensated cirrhosis and ACLF. (10,14,29,43,44) Although there are no studies, to our knowledge, specifically examining Angpt-2/Tie2 interventions in combined liver-kidney injury animal models, our prospective human findings suggest that this pathway may be similarly important in HRS/AKI and cirrhosis.…”
Section: Survival Daysmentioning
confidence: 73%
See 1 more Smart Citation
“…Survival Probability syndrome, and disseminated intravascular coagulation, Angpt-2 upregulation and Tie2 inhibition have been linked to thrombocytopenia, increased INR, elevated D-dimer, overexpression of pro-inflammatory cytokines, multisystem organ dysfunction (e.g., AKI), decreased systemic circulating blood pressure, and ultimately poorer survival; conversely, interventions to restore or enhance Tie2 signaling not only ameliorate these abnormalities but also improve survival. (16,18,23,42) Strikingly, this same constellation of features is present among patients with decompensated cirrhosis and ACLF. (10,14,29,43,44) Although there are no studies, to our knowledge, specifically examining Angpt-2/Tie2 interventions in combined liver-kidney injury animal models, our prospective human findings suggest that this pathway may be similarly important in HRS/AKI and cirrhosis.…”
Section: Survival Daysmentioning
confidence: 73%
“…As a cell‐surface receptor modulated by secreted ligands, Tie2 and Angiopoietins constitute a highly promising set of candidate drug targets for human disease. In experimental models of sepsis, systemic inflammatory syndrome, and disseminated intravascular coagulation, Angpt‐2 upregulation and Tie2 inhibition have been linked to thrombocytopenia, increased INR, elevated D‐dimer, overexpression of pro‐inflammatory cytokines, multisystem organ dysfunction (e.g., AKI), decreased systemic circulating blood pressure, and ultimately poorer survival; conversely, interventions to restore or enhance Tie2 signaling not only ameliorate these abnormalities but also improve survival . Strikingly, this same constellation of features is present among patients with decompensated cirrhosis and ACLF .…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge regarding hemorrhagic shock-induced hyperpermeability is restricted to animal studies [14][15][16][17][18] or in vitro studies investigating the effect of rodent plasma on endothelial barrier function [19]. Animal studies showed an early increase in endothelial permeability following hemorrhagic shock [14,15], which even further increased following fluid resuscitation [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Vasculotide, an angiopoietin-1 mimetic, is a recently introduced drug that functions by promoting Tie2 phosphorylation and subsequently restores or promotes endothelial stability as shown by reduced vascular leakage in animal models of sepsis, 13 acute kidney 14 or lung injury, 15 and haemorrhagic shock. 16 Although patient studies also suggested a possible important role of the angiopoietin/Tie2 system in CPB patients, this has not been confirmed using a therapeutic strategy. 4,7,9e12 We therefore aimed to investigate the relationship between Tie2 regulation and microcirculatory perfusion in a rat CPB model.…”
mentioning
confidence: 99%